Off-label use of psychotropic drugs beyond officially approved indications in Colombia (2017)
Introduction: Off-label use of psychotropic drugs is a common practice. In Colombia, no information is available in this regard.Objective. To describe off-label use of psychoactive drugs in a health promoting entity (EPS in Spanish) in Bogotá D.C.Materials and methods: Cross sectional, observational study (prescription-indication), including a random sample of patients prescribed with psychotropic drugs between January and June 2010. Sociodemographic, clinical, pharmacological and concordance variables were evaluated (correlation between use indication and approved indication). Multivariate analyzes were performed looking for an association with off-label prescriptions.Results: 420 evaluated patients had a mean age of 44.2±18.8 years, with female predominance (67.9%). Off-label prescription was found in 58.6-59.8% of cases. 84.3% of the prescriptions were delivered by general practitioners. The main psychoactive drugs prescribed for conditions such as tension headaches and insomnia were amitriptyline (n=128, 86.7% of off-label use), trazodone (n=93, 88.2%) and fluoxetine (n=66, 36.4%). The multivariate analysis found that being a young adult (OR=1.99, 95%CI: 1.06-3.70; p=0.030), being treated by general medicine (OR=3.40, 95%CI: 1.50-7.67; p=0.003) and being prescribed with amitriptyline (OR=11.38; 95%CI: 5.06-25.58; p0.001) or trazodone (OR = 13.08; 95%CI: 5.23-32.68; p0.001) increased the likelihood of receiving an off-label prescription.Conclusions: Psychotropic drugs in Bogotá are used, to a great extent, as off-label in indications other than those officially approved. Thus, it is important to strengthen education and control to achieve a rational, effective and safe use of drugs.